Strategi Kepala Madrasah dalam Meningkatkan Mutu Pendidikan Madrasah - Nazib, Fiqra Muhamad; Saifullah, Iman; Nasrullah, Yufi Mohammad; Hanifah, Farah (Indo-MathEdu Intellectuals Journal, 2023)
This research aims to analyze the literature review of madrasa head strategies in improving the quality of madrasa education. This research method uses Systematic Literature Review (SLR) with stages of determining themes, searching, selecting literature, analysis, and interpretation, drafting, and disseminating results. The research was conducted using 20 articles resulting from a selection of 38 articles obtained from various sources with publication years from 2016-2022. The focus of the study is on 3 things, namely programs, strategies, and implications of the madrasa head's strategy in improving the quality of education. The results of the research show that: 1) the programs implemented by madrasah heads are diverse and varied, most madrasah heads produce quality madrasahs by first improving the quality and competence of their teachers. 2) the madrasa head's strategy for achieving madrasa quality has its own characteristics depending on the type, leadership style and environment of the madrasa. 3) the implications of the madrasa head have a direct impact on the quality of education in the madrasa, both human resources, academic and non-academic